Tiny golden angle ultrashort echo‐time lung imaging in mice. (28th July 2021) - Balasch, Anke; Metze, Patrick; Li, Hao; Rottbauer, Wolfgang; Abaei, Alireza; Rasche, Volker
Abstract : Imaging the lung parenchyma with MRI is particularly difficult in small animals due to the high respiratory and heart rates, and ultrashort T2* at high magnetic field strength caused by the high susceptibilities induced by the air–tissue interfaces. In this study, a 2D ultrashort echo‐time (UTE) technique was combined with tiny golden angle (tyGA) ordering. Data were acquired continuously at 11.7 T and retrospective center‐of‐k‐space gating was applied to reconstruct respiratory multistage images. Lung (proton) density ( f P ), T2*, signal‐to‐noise ratio (SNR), fractional ventilation (FV) and perfusion ( f ) were quantified, and the application to dynamic contrast agent (CA)‐enhanced (DCE) qualitative perfusion assessment tested. The interobserver and intraobserver and interstudy reproducibility of the quantitative parameters were investigated. High‐quality images of the lung parenchyma could be acquired in all animals. Over all lung regions a mean T2* of 0.20 ± 0.05 ms was observed. FV resulted as 0.31 ± 0.13, and a trend towards lower SNR values during inspiration (EX: SNR = 12.48 ± 6.68, IN: SNR = 11.79 ± 5.86) and a significant ( P  < 0.001) decrease in lung density (EX: f P  = 0.69 ± 0.13, IN: f P  = 0.62 ± 0.13) were observed. Quantitative perfusion results as 34.63 ± 9.05 mL/cm 3 /min (systole) and 32.77 ± 8.55 mL/cm 3 /min (diastole) on average. The CA dynamics could be assessed and, because of the continuous nature of the data acquisition, reconstructed at different temporal resolutions. Where a good to excellent interobserver reproducibility and an excellent intraobserver reproducibility resulted, the interstudy reproducibility was only fair to good. In conclusion, the combination of tiny golden angles with UTE (2D tyGA UTE) resulted in a reliable imaging technique for lung morphology and function in mice, providing uniform k‐space coverage and thus low‐artefact images of the lung parenchyma after gating. Abstract : The feasibility of 2D tyGA UTE for the assessment of lung (proton) density, fractional ventilation, quantitative perfusion and qualitative contrast‐enhanced perfusion at 11.7 T was successfully investigated in mice. Lung parenchyma T2* was quantified for correct signal decay compensation during density calculation. Inter‐ and intra‐reader and interstudy reproducibility were assessed, showing the accuracy of the investigated approach.